A Lesson for the King: Sotades’ Invective against Ptolemy (fr. 1 and 16 Powell) and Callimachus’ “Epigram” 1 Pfeiffer - Kwapisz, Jan (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2009)
The paper discusses the fable-like form of Callimachus’ Epigram 1 Pfeiffer and of Sotades’ fragmentary Invective against Ptolemy, and suggests that the former poem may contain an allusion to the latter. In the light of this reading, both poems are to be viewed as playfully encouraging the Ptolemies’ incestuous marriage.

The present discussion develops Roberto Pretagostini’s proposal of reconstructing Sotades’ invective against Ptolemy as beginning with fr. 16 and ending with fr. 1 Powell, and his suggestion that Callimachus, fr. 75.4–5 Pfeiffer contains an allusion to Sotades’ poem. An examination of Callimachus’ Epigram 1 shows on the one hand that it can be read as a jocular comment on the Ptolemies’ marriage, and on the other that its form is conventional and typical of the early Greek fable. Since Sotades’ invective appears to share these characteristics, it is argued that Epigram 1 is another instance of when Callimachus alludes to Sotades.
Keywords: callimachus; sotades; Hellenistic poetry; ancient fable